Perbandingan Pemberian Tablet Fe dan Mengkonsumsi Sayuran Kalakai (Stenochlaena palustris) Pada Ibu Hamil Terhadap Kenaikan Kadar Hb Di Puskesmas Gambut - Akhmad Mahyuni; Sugeng Riyanto; Muhhalimah Muhhalimah (Jurnal Kesehatan Indonesia, 2015)
Iron Deficiency Anemia (ABD) remains a public health problem with respect to the high prevalence and its impact on the health of mothers and their babies. How to prevent iron deficiency in pregnant women by administering daily 1 tablet Fe 90 days of pregnancy. Eat foods that contain lots of iron from animal foods According Dessy et al that the iron content of 291,32 mg per 100 mg of material, allowing for the prevention of anemia. This study aims to determine the ratio between the provision of iron tablet and consuming vegetables kalakai (Stenochlaena palustris) in pregnant women to rise in Hb levels in Public Health Centers Gambut 2015. This study uses Quasy experimental design with pretest-posttest design. In this study, samples were measured in this study is the second trimester pregnant women were anemic (<10,5gr%) as many as 24 people were divided into 2 groups: group A were given a tablet Fe and group B were given kalakai vegetable for 22 days. Data were analyzed using T- test, Test Dependent and Independent T-test. The statistical results showed that there is a significant increase in the average hemoglobin levels before and after treatment in both groups (p = 0,000), but the increase in hemoglobin levels were not different both treatment groups (p = 0,262). After giving the Fe tablet and kalakai vegetables no elevated levels of hemoglobin but the increase was not significantly different between treatment groups. Giving Fe needs to be continued and necessary extension of knowledge about nutrition in kalakai vegetables and health and food intake.